2021
DOI: 10.3389/fphys.2021.778872
|View full text |Cite
|
Sign up to set email alerts
|

A Fully-Coupled Electro-Mechanical Whole-Heart Computational Model: Influence of Cardiac Contraction on the ECG

Abstract: The ECG is one of the most commonly used non-invasive tools to gain insights into the electrical functioning of the heart. It has been crucial as a foundation in the creation and validation of in silico models describing the underlying electrophysiological processes. However, so far, the contraction of the heart and its influences on the ECG have mainly been overlooked in in silico models. As the heart contracts and moves, so do the electrical sources within the heart responsible for the signal on the body sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…There was inconsistent timing of exercise stress test in RTOF patients, although the time interval between CMR and stress tests were still within recommended surveillance guidelines of RTOF patients ( 45 ) and unlikely to alter results based on previous longitudinal studies ( 46 , 47 ). As the RV kinematic reconstruction is driven by imaging, the current methodology does not couple electrical propagation with mechanical contraction ( 48 , 49 ), which may explain the lack of correlation between HDF and QRS duration. Most importantly, we did not interpret the systolic HDF in this cohort – this was partly due to concern that subtle deviations in feature tracking during early systole were amplified by second order effects contributing to systolic discrepancies shown in Figure 8 .…”
Section: Discussionmentioning
confidence: 99%
“…There was inconsistent timing of exercise stress test in RTOF patients, although the time interval between CMR and stress tests were still within recommended surveillance guidelines of RTOF patients ( 45 ) and unlikely to alter results based on previous longitudinal studies ( 46 , 47 ). As the RV kinematic reconstruction is driven by imaging, the current methodology does not couple electrical propagation with mechanical contraction ( 48 , 49 ), which may explain the lack of correlation between HDF and QRS duration. Most importantly, we did not interpret the systolic HDF in this cohort – this was partly due to concern that subtle deviations in feature tracking during early systole were amplified by second order effects contributing to systolic discrepancies shown in Figure 8 .…”
Section: Discussionmentioning
confidence: 99%
“…In our simulation setup, we did not consider motion and contraction of the atria for the sake of reducing model complexity and computational cost. Moss et al showed that a fully coupled electro-mechanical model does not have any influence on simulation results regarding atrial activation and that resulting P waves exhibit negligible differences to the ones computed on a non-deforming model [56]. However, the atrial repolarization results of our study might be affected to a larger extent by the lack of a coupled model as previous studies reported a substantial impact of mechanical feedback on electrophysiological behavior in the ventricles [57], [58], especially during the repolarization phase [56], [59].…”
Section: Limitationsmentioning
confidence: 99%
“…The O'Hara Rudy model also serves as the consensus base model for the Comprehensive in Vitro Proarrhythmia Assay initiative established to develop a new paradigm for assessing proarrhythmic risk [58,59]. Despite its use as the consensus base model, novel updates to this model have recently been proposed which report dynamic drug-IKr interactions and a re-assessment of the myocardial pro-arrhythmic sensitivity to I Kr blockage [60,61], sex differences in drug-sensitive cardiomyocyte ion channel current densities [7], and apico-basal heterogeneity in the slow delayed rectifying potassium channel conductance [62]. These aspects might affect the critical drug concentration at which arrhythmia start developing in this study.…”
Section: Mechanical Drug Effectsmentioning
confidence: 99%